2012
DOI: 10.1152/ajpcell.00263.2011
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of KV1.3 channels by protein kinase A I in T lymphocytes is mediated by the disc large 1-tyrosine kinase Lck complex

Abstract: The cAMP/PKA signaling system constitutes an inhibitory pathway in T cells and, although its biochemistry has been thoroughly investigated, its possible effects on ion channels are still not fully understood. K(V)1.3 channels play an important role in T-cell activation, and their inhibition suppresses T-cell function. It has been reported that PKA modulates K(V)1.3 activity. Two PKA isoforms are expressed in human T cells: PKAI and PKAII. PKAI has been shown to inhibit T-cell activation via suppression of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“…Furthermore, a similar effect was observed with the PKAI inhibitor Rp-8Br-cAMP (100 μM, Fig. 4B) (38). …”
Section: Resultssupporting
confidence: 73%
“…Furthermore, a similar effect was observed with the PKAI inhibitor Rp-8Br-cAMP (100 μM, Fig. 4B) (38). …”
Section: Resultssupporting
confidence: 73%
“…Our results are also supported by a previous study, which demonstrated that although Kv1.3 blockers do not prevent immunological synapse formation, they suppress Ca 2+ signalling, cytokine production and proliferation of T EM cells . For a detailed Kv1.3 mechanism of T‐cell functional modulation mediated by Kv1.3/Dgl1/Lck complex, see Kuras et al 2012 …”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the cease or altered kinetics of the redistribution of Kv1.3 channels during engagement of T cells in immunological synapse can also modify Ca 2+ ‐responses. In addition, a scaffolding protein of Kv1.3 (Dlgh1/CARMA‐1), which can bind and couple various protein kinases to the channel, such as p56lck and PKA, was demonstrated to promote NFAT activation (54, 57, 58). Based on these, we suppose that the control of Kv1.3 current in Th1 cell lineage may be due to the modification of the channel by protein kinases, rather than targeting to distinct lipid compartments, although it cannot be excluded, either.…”
Section: Discussionmentioning
confidence: 99%